"Because She's One Who Listens": Children Discuss Disclosure Recipients in Forensic Interviews. (November 2013) - Malloy, Lindsay C.; Brubacher, Sonja P.; Lamb, Michael E.
The current study examined investigative interviews using the National Institute of Child Health and Human Development (NICHD) Investigative Interview Protocol with 204, five- to thirteen-year-old suspected victims of child sexual abuse. The analyses focused on who children told, who they wanted (or did not want) to tell and why, their expectations about being believed, and other general motivations for disclosure. Children's spontaneous reports as well as their responses to interviewer questions about disclosure were explored. Results demonstrated that the majority of children discussed disclosure recipients in their interviews, with 78 children (38%) explaining their disclosures. Only 15 children (7%) mentioned expectations about whether recipients would believe their disclosures. There were no differences between the types of information elicited by interviewers and those provided spontaneously, suggesting that, when interviewed in an open-ended, facilitative manner, children themselves produce informative details about their disclosure histories. Results have practical implications for professionals who interview children about sexual abuse.